The Textbook Conundrum: CSD Students' Textbook Preferences - Tapp, Julie (Valdosta, GA: Valdosta State University, 2016)
The Textbook Conundrum: CSD Students' Textbook Preferences. Julie Tapp. Valdosta State University Undergraduate Symposium Posters, 2016.
Keywords: Posters; College students--Research; Microsoft PowerPoint (Computer file); Undergraduates